Religiously deviant or a cult? a corpus-based collocational analysis of the representation of GISBH in Malaysian English and Malay news reports - Sook, Christina Beng Ong; Hajar Abdul Rahim (Penerbit Universiti Kebangsaan Malaysia, 2025)
Global Ikhwan Services and Business Holdings (GISBH), a Malaysian conglomerate known for operating a wide range of businesses in accordance with Islamic principles, came under intense media scrutiny in September 2024 following a police operation that uncovered allegations of child abuse in care homes under its management. The incident reignited public discourse surrounding GISBH’s historical links to the banned Al-Arqam sect, which has been widely described by Malaysian Muslim scholars and organisations as religiously deviant or cult-like. Given this and the central role of Islam in Malay cultural identity in Malaysia, the current study examined how GISBH is represented in Malay-language media in comparison to its portrayal in English-language outlets in Malaysia. Drawing on West and Langone’s (1986) conceptualisation of cults and Langone’s (2015) framework of cult characteristics and using corpus linguistics techniques, namely collocational analysis, this study analyses the representation of GISBH in a corpus of Malay and English news reports published between September and November 2024. The analysis involved identifying collocates of the term “GISBH” in each language, categorising concordance lines according to Langone’s cult characteristics, and thematically evaluating them based on West and Langone’s core elements of cultic groups. The findings show that religious themes were minimal. While the data suggest GISBH is portrayed as non-conformist and cult-like, neither sub-corpus explicitly used the term, and overall representations were similar across both languages.